Barrier evolution of Cape San Blas, Saint Joseph Peninsula, Florida from textural analysis, ground penetrating radar and organic matter isotope geochemistry - Ahmad, Shakeel (My University, 2012)
St. Joseph peninsula is situated on the panhandle of Florida west coast in the northeastern Gulf of Mexico at N29°50‘ and W85°20‘ and is located at the west edge of the westernmost portion of the Apalachicola Barrier Island Complex (ABIC) on the Gulf of Mexico shoreline. Three vibra-cores were collected on Saint Joseph Bay side of Cape San Blas which is part of St. Joseph peninsula to determine its evolution in context of previous work by Rink and Lopez (2010). The study uses detailed textural analysis (PSD - Particle Size Distribution plots), multivariate statistics on the PSDs (Q-mode cluster analysis) and organic matter geochemistry (C/N and δ13C). In addition, Ground Penetrating Radar (GPR) profiles are used to provide broader stratigraphic context.
The stratigraphic analysis found that CSB has an older nucleus of strandplain deposits dating to >12 Ka that were subsequently flooded and modified through Holocene sea-level rise at ≈ 2.2 Ka. Actual barrier formation began sometime between 2.2. Ka and 0.6 Ka which is the oldest beach ridge measured by Rink and Lopez (2010). Progradation of the barrier on the St Joseph Bay side began at least by 0.3 Ka and likely earlier. There is no evidence to indicate a higher than present sea-level in our core data and our data follows that of other sea-level studies using submerged offshore samples
Keywords: Sea level; Holocene; Gulf of Mexico; barrier evolution; textural analysis; ground penetrating radar; organic matter isotope geochemistry